Transcriptomic profile of symbiotic accessory nidamental gland during female maturation in bigfin reef squid - Tseng, Peng-Wei; Li, Hau-Wen; Chen, Chih; Tseng, Yung-Che; Chang, Ching-Fong; Wu, Guan-Chung (Frontiers in Marine Science, 2023)
The bigfin reef squid, Sepioteuthis lessoniana, are a valuable commercial species in East Asian regions such as Taiwan and Japan. A lack of genomic information limits the application of potential aquaculture techniques, especially in breeding when considering the hatching rate of offspring. In some squids and cuttlefishes, symbiotic bacteria are transmitted from the accessory nidamental gland (ANG) to the jelly coat of eggs. In Hawaiian bobtail squid, these parent-delivered mutualistic bacteria play an important role in preventing lethal biofouling of the eggs and accelerating the hatch rate of offspring. The bacterial consortium, which is housed in the female squids ANG, are governed by host selection during female maturation. Immune functions are typically used to explain the regulatory mechanism of symbioses by host selection. In this study, we evaluated the transcripts featured in bacterial selection and maintenance during ANG development using RNA-seq. Different developmental stages of ANGs (stages 1–4) were sequenced. The de novo transcriptome assembly resulted in 524,918 unigenes. Two groups, non-pigmentation group (stage 1 and stage 3) and pigmentation group (stage 4), were clustered by transcriptome-wide expression profile analysis. The gene expression analyses indicated that 9,475 differential expression genes (DEGs) in three different phases and 1,363 (14.3%) DEGs were matched in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Furthermore, KEGG-enriched analysis results suggested that immune responses are a dominant pathway in the non-pigmentation group (stage 1 and stage 3) whereas lipid metabolism and metabolism of flora fermentation are dominant in the pigmentation group (stage 4). Although the host immunity plays an important role during bacterial colonization of the ANG in bigfin reef squid, our results showed that most immune-related genes had a reduced transcriptomic level in the pigmentation group compared with the non-pigmentation group. Therefore, our results provide new insight to understand the regulatory mechanisms of initial bacterial colonization and later bacterial pigmentation in the bigfin reef squid.